2012
DOI: 10.5539/jfr.v1n2p291
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioavailability of Mineral Nutrients in Breakfast Cereals

Abstract: The bioavailability of both micro-and macroelements was investigated under conditions simulating the digestion processes in the human alimentary system. A one-step enzymatic extraction was applied using buffered solutions containing pepsin, trypsin, α-amylase or pancreatin, which are enzymes that hydrolyse different nutritional food components such as peptides, carbohydrates and lipids, as the extractant. Corn flakes and multigrain breakfast cereals containing taste additives from a local market in the Wroclaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The analyzed breakfast cereals contained on average 4.5 ± 1.6 mg Cu, 21.4 ± 18.1 mg Mn, 29.3 ± 12.9 mg Fe, and 20.2 ± 11.7 mg Zn per 1 kg of fresh weight of the product (Table 3 ), which can be represented as Fe > Mn > Zn > Cu. Studies carried out in Poland and presented by Leśniewicz et al [ 40 ] showed an identical relationship. According to those authors, breakfast cereals contained on average 1.67–167 mg Fe, 0.34–15.8 mg Mn, 0.21–14.4 mg Zn, and 0.10–3.67 mg Cu per 1 kg.…”
Section: Resultsmentioning
confidence: 63%
“…The analyzed breakfast cereals contained on average 4.5 ± 1.6 mg Cu, 21.4 ± 18.1 mg Mn, 29.3 ± 12.9 mg Fe, and 20.2 ± 11.7 mg Zn per 1 kg of fresh weight of the product (Table 3 ), which can be represented as Fe > Mn > Zn > Cu. Studies carried out in Poland and presented by Leśniewicz et al [ 40 ] showed an identical relationship. According to those authors, breakfast cereals contained on average 1.67–167 mg Fe, 0.34–15.8 mg Mn, 0.21–14.4 mg Zn, and 0.10–3.67 mg Cu per 1 kg.…”
Section: Resultsmentioning
confidence: 63%
“…These values for magnesium are close to 30% extraction efficiency of magnesium (mg) when pepsin was used to digest ready-to eat breakfast cereals. Lower than 50% extraction efficiency was reported for phosphorous by Lesniewicz et al (2012). Although, plantain had been reported to contain high amount of iron (Fe) and potassium (k) by so many workers (Ogazi, 1984;Izonfouand Omauru, 1988;Baiyeri 2000;Adeniji et al, 2007), the proportions in soluble forms after enzymatic digestion of plantain products studied, suggests that not all the minerals are bioavailable, and absorbed by the intestinal cells.…”
Section: Bioavailability Of Mineralsmentioning
confidence: 98%
“…Cornflakes are small flat pieces of maize that are eaten with milk as a breakfast cereal or toasted flakes made from the coarse meal of hulled corn for use as a breakfast cereal (McKevith, 2004;Leśniewicz, 2012). Cornflakes are good sources of vitamins, minerals, folate, dietary fiber, as well as proteins, and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%